Caracterización agronómica de 95 accesiones en el banco de germoplasma de café en Chanchamayo (Perú), año 2016 - Alvarado y Cols., L. (2018)
The present study aimed to evaluate the agronomic characteristics of 95 accessions in the coffee germplasm bank (Coffea arabica L.) in Chanchamayo, in 2016. This work was carried out in "La Genova" fund of the National Agrarian University La Molina in San Ramón-Chanchamayo. The characterization was carried out on the basis of characters that describe the productive capacity of the plant and its behavior against the "drill" (Hypothenemus hampei) and "rust" (Hemileia vastatrix). An analysis of variance and a Duncan test were performed for each variable studied using the Statgraphic program. Then a multivariate analysis (main components and groupings) was carried out with the NTSYS program that allowed to know the characters that have expressed a greater degree of variability, as well as the relation between accessions. The accessions with the highest yields in average coffee cherry / plant were UNACAF-70 with 5.42 kg / plant and UNACAF149 with 4.16 kg / plant; While the least outstanding accessions were UNACAF-151 with 0.22 kg / plant and UNACAF-223 with 0.15 kg / plant. Regarding the weight of dry parchment coffee per plant, the most outstanding accession remained UNACAF-70 with 1.1 kg / plant. Finally, the most discriminating characters were cherry coffee weight, dry parchment coffee weight, number of fruits per plant, pulp weight of 100 mature fruits and weight of 100 mature fruits.